Using the Maslach Burnout Inventory among dentists: burnout measurement and trends - te Brake JHM, Bouman AM, Gorter RC, Hoogstraten J, Eijkman MAJ (Blackwell Synergy, 2008)
To extend our knowledge about the applicability of the Maslach Burnout Inventory (MBI) among dentists and to investigate trends in burnout risk among dental professionals.